Protective Effects against the Development of Alzheimer's Disease in an Animal Model through Active Immunization with Methionine-Sulfoxide Rich Protein Antigen - Adam S. Smith; Kyle R. Gossman; Benjamin Dykstra; Fei Philip Gao; Jackob Moskovitz (MDPI AG, 2022)
The brain during Alzheimer's disease (AD) is under severe oxidative attack by reactive oxygen species that may lead to methionine oxidation. Oxidation of the sole methionine (Met35) of beta-amyloid (Aβ), and possibly methionine residues of other extracellular proteins, may be one of the earliest events contributing to the toxicity of Aβ and other proteins in vivo. In the current study, we immunized transgenic AD (APP/PS1) mice at 4 months of age with a recombinant methionine sulfoxide (MetO)-rich protein from Zea mays (antigen). This treatment induced the production of anti-MetO antibody in blood-plasma that exhibits a significant titer up to at least 10 months of age. Compared to the control mice, the antigen-injected mice exhibited the following significant phenotypes at 10 months of age: better short and long memory capabilities; reduced Aβ levels in both blood-plasma and brain; reduced Aβ burden and MetO accumulations in astrocytes in hippocampal and cortical regions; reduced levels of activated microglia; and elevated antioxidant capabilities (through enhanced nuclear localization of the transcription factor Nrf2) in the same brain regions. These data collected in a preclinical AD model are likely translational, showing that active immunization could give a possibility of delaying or preventing AD onset. This study represents a first step toward the complex way of starting clinical trials in humans and conducting the further confirmations that are needed to go in this direction.